A randomised trial to investigate the efficacy of magnesium sulphate for refractory ventricular fibrillation. Issue 1 (1st January 2002) - Hassan, T B; Jagger, C; Barnett, D B
Abstract : Background: Ventricular fibrillation (VF) remains the most salvageable rhythm in patients suffering a cardiopulmonary arrest (CA). However, outcome remains poor if there is no response to initial defibrillation. Some evidence suggests that intravenous magnesium may prove to be an effective antiarrhythmic agent in such circumstances. Study hypothesis: Intravenous magnesium sulphate given early in the resuscitation phase for patients in refractory VF (VF after 3 DC shocks) or recurring VF will significantly improve their outcome, defined as a return of spontaneous circulation (ROSC) and discharge from hospital alive. Design: A randomised, double blind, placebo controlled trial. Pre-defined primary and secondary endpoints were ROSC at the scene or in accident and emergency (A&E) and discharge from hospital alive respectively. Setting, participants, and intervention: Patients in CA with refractory or recurrent VF treated in the prehospital phase by the county emergency medical services and/or in the A&E department. One hundred and five patients with refractory VF were recruited over a 15 month period and randomised to receive either 2–4 g of magnesium sulphate or placebo intravenously. Results: Fifty two patients received magnesium treatment and 53 received placebo. The two groups were matched for most parameters including sex, response time for arrival at scene and airway interventions. There were no significant differences between magnesium and placebo for ROSC at the scene or A&E (17% v 13%). The 4% difference had 95% confidence intervals (CI) ranging from −10% to +18%. For patients being alive to discharge from hospital (4% v 2%) the difference was 2% (95% CI –7% to +11%). After adjustment for potential confounding variables (age, witnessed arrest, bystander cardiopulmonary resuscitation and system response time), the odds ratio (95% CI) for ROSC in patients treated with magnesium as compared with placebo was 1.69 (0.54 to 5.30). Conclusion: Intravenous magnesium given early in patients suffering CA with refractory or recurrent VF did not significantly improve the proportion with a ROSC or who were discharged from hospital alive.